IMPLEMENTASI KOPERASI PONDOK PESANTREN SEBAGAI ASPEK PEMBELAJARAN - Aep Tata , Suryana; Siti Najmi Nurul , Khotimah; Windi Septiani , Nurjanah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
Cooperatives are one form of economic organization that is important in improving the social and economic welfare of members. In the boarding school environment, cooperatives play a role in sharia-based economic development, including the application of sharia entrepreneurship principles that prioritize Islamic economic values. This article discusses the management of boarding school cooperatives as a means of theoretical and practical learning for students in developing entrepreneurial skills based on sharia. The study also highlights the cooperative implementation model at Al-Ittifaq Islamic Boarding School in Bandung as an example of real implementation. This research uses a literature study method with a qualitative analysis approach. The results showed that the boarding school cooperative can increase the economic independence of students while providing benefits to the surrounding community